Hydroclimate Variability Affects Habitat‐Specific (Open Water and Littoral) Lake Metabolism. Issue 1 (5th January 2022) - Scordo, Facundo; Lottig, Noah R.; Fiorenza, Juan E.; Culpepper, Joshua; Simmons, James; Seitz, Carina; Krynak, Edward M.; Suenaga, Erin; Chandra, Sudeep
Abstract: Lakes integrate the signals of changing hydroclimate in their surrounding basin, which substantially influence gross primary production (GPP), respiration (R), and net ecosystem production (NEP). Most research focuses only on the changes to the open water habitat despite the littoral habitat's importance to lakes and its sensitivity to hydroclimatic variability. We analyze how years with different ice‐out dates and snow water equivalent (SWE) triggered different metabolism responses in the open water and littoral habitats of a subalpine lake. The dry (early ice‐out date and low SWE) and wet (late ice‐out date and high SWE) years had lower GPP and R rates in both habitats compared to the average hydroclimatic year. Furthermore, consumer biomass decreased during dry and wet years. GPP and R reduced the most in the littoral habitat. Consequently, the relative contribution to total lake GPP and R of the littoral habitat decreased, and the contribution of the open water habitat increased during the dry and wet years. We demonstrate that hydroclimatic conditions affect productivity and consumer biomass and show that within‐lake habitats do not experience equivalent responses to climate forcing. Our study has implications for how ecosystem scientists and managers quantify the absolute and relative contributions of the littoral habitat to whole lake production in the context of climate variation. Plain Language Summary: Lakes integrate climate variability at the catchment scale. These large‐scale changes influence the food production and consumption (i.e., metabolism) of lake habitats both at the nearshore and open water. While the shallow nearshore habitat is recognized as an important site for food production, the offshore habitat remains the focus of many lake studies We analyzed how years with different climatic conditions (dry and wet) affected metabolism in the nearshore and offshore habitats of a mountain lake. During dry and wet years, the food production and consumption in both habitats was lower compared to a year with average climatic conditions. Furthermore, animal biomass decreased during dry and wet years and the nearshore bottom habitat was more sensitive to changes with a large reduction in food production. We demonstrate that climatic conditions lead to differential impacts within‐lake habitats. Thus, lake management may be deficient if only one habitat is studied. Key Points: Within‐lake habitats do not have equivalent responses to climate forcing Primary production and respiration of the littoral habitat shows greater sensitivity to hydroclimate changes than the open water habitat Littoral net ecosystem production can change from autotrophic under dry conditions to heterotrophic under wet conditions